Parental Satisfaction with Neonatal Intensive Care Unit Services and Associated Factors in Jimma University Medical Center, Ethiopia - Adal Z; Atomsa G; Tulu G (Dove Medical Press, 2022)
Zinash Adal,1 Gamechu Atomsa,1 Gemechu Tulu2 1School of Nursing, Faculty of Health Science, Jimma Institute of Health, Jimma University, Jimma, Ethiopia; 2Kuyu General Hospital, Oromia Regional Health Bureau, Oromia, EthiopiaCorrespondence: Gemechu Tulu, Kuyu General Hospital, Oromia Regional Health Bureau, Gerba Guracha, Ethiopia, Tel +251-901-142-299, Email gemechutul@gmail.comBackground: Patient satisfaction is an important aspect of the quality of care in the inpatient setting. In neonatal intensive care units (NICUs), parent satisfaction and their experiences are fundamental to assessing clinical practice and improving the quality of care delivered to infants and parents. In developing countries like Ethiopia, the satisfaction of parents of neonates requiring intensive care is often overlooked. Thus, the study aimed to assess parental satisfaction with neonatal intensive care unit services and associated factors.Methods: A hospital-based, cross-sectional study was conducted at Jimma University Medical Center from July to August, 2021. Parents of admitted newborn infants were selected by convenience sampling. Data were collected using a structured questionnaire adapted from Empowerment of Parents in Intensive Care (EMPATHIC). Data were entered into Epidata 4.6 and exported into SPSS Version 25 for analysis. Bi-variable and multivariable logistic regression analyses were used to identify factors associated with parental satisfaction.Results: Of 122 eligible parents, 114 (93.5%) participated. Parental satisfaction with NICU services was 57.9% [95% CI: (49.1%, 66.7%)]. More than half (60.5%) of the parents responded that their baby gets better care in the incubator/bed. Compassionate and respectful care [AOR = 5.88, 95% CI: (2.19- 15.78)] was significantly associated with parental satisfaction.Conclusion: A sizable proportion of the parents was not satisfied with the services of the neonatal intensive care unit at Jimma Medical Centre. Compassionate and respectful care is associated with parental satisfaction. The results of this study support strengthening a culture of family-centered care via compassionate and respectful care.Keywords: Jimma Medical Center, parental satisfaction, neonatal intensive care unit, Ethiopia